Valuation of Endowment-Insurance Equity-Linked Contracts for Stocks with Exotic Dynamics - Javier Villarroel (The Scientific World Journal)
We consider the fair martingale prize of insurance contracts with benefit received either at the insurer’s demise or at maturity. We show how to modify the dynamics of the underlying so as to incorporate the possibility that the traded stock has a strong support at some level. The resulting dynamics is integrated and the fair prize of several natural endowment-insurance contracts is obtained.